Analisis Investasi Pembangunan Jalur Ganda Kereta Api Tanjung Karang Kertapati (Segmen Tanjung Karang – Prabumulih) - Nurmagita Pamursari; Rahayu Sulistyorini (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2019)
Train is one of the most preferred modes of transportation for the people of Lampung. One of the efforts made by PT KAI in improving service quality was to build a double railroad track for Tanjung Karang - Kertapati train. The purpose of this study is to find out the analysis of the invest - ment feasibility of the double track construction carried out by PT KAI. The data used is the price data for the construction of the railway line per kilometer and the income data of PT. KAI from passenger trains and babaranjang. The parameters used to review investment are using the Net Present Value (NPV) method, Benefit to Cost Ratio (BCR), Internal Rate of Return (IRR) and, Payback Period (PP). There are 8 (eight) scenarios in calculating the investment feasibility analysis in this study. Each scenario has a variation on the inflation rate and the occupancy rate (KTD) and the achievement of the volume of coal transport. The results of the investment feasibility analysis carried out, all scenarios are very profitable, but the most favorable scenario is scenario 8, with the source of investment funds coming from own funds, 100% KTD, 5% inflation rate, 25 million tons / year coal volume, and rate of return by 15%.